ЕТНОНИМИ И ЕТНИЧКА ИДЕНТИФИКАЦИЈА НА РОМСКОТО НАСЕЛЕНИЕ ВО МАКЕДОНИЈА (Philological Studies, 2019)
The paper, based on my own field research conducted from 2010 to 2013, and enriched with data from available sources, focuses on the ethnonyms and ethnic identification of the Romani population in Macedonia. As a factor in identification and symbolic differentiation, this terminology contributes to the positioning of the different Roma groups, below or above on the value scale of saidcommunity. At the same time, the paper shows the socio-cultural images of the Romani way of life within the community itself as well as the wider perception of it by “others”.
Keywords: Roma groups, ethnonyms, exonyms